Hospice policy and patterns of care - Hays, Judith C (Journal of Nursing Scholarship, 1986)
Hospice providers and policy makers are currently evaluating the emerging patterns of hospice care, especially regarding cost containment considerations. This study compared patterns of care for two groups of hospice homecare clients–one group, which received only homecare services for the duration of the hospice career; the other, which received both hospice homecare and inpatient services. The groups were significantly different on clinical parameters, number of homecare episodes, survival rate, and place of death. The impact of policy structures on continuity of care and service equity are discussed. Copyright © 1986, Wiley Blackwell. All rights reserved
Keywords: Aged; Comparative Study; Connecticut; Cost Control; Female; Home Care Services; Hospices; Hospitalization; Human; Male; Middle Age; Public Policy; United States; adult; aged; article; comparative study; cost control; dept.nur; economics; female; home care; hospice; hospitalization; human; male; organization and management; policy; utilization review